‘We Have Spoken So Long O God: When Will We Be Heard?’ Theological Reflections on Overcoming Violence against Women - Gnanadason, Aruna (Theology & sexuality, 2006)
This article summarizes some of the major theological challenges women have attempted to address over the years in dealing with violence against women. From drawing strength from the biblical promise that women are ‘made in the image of God’ to reinterpreting doctrines such as sin, Christology, atonement, salvation and healing, women have attempted to speak a word of hope for victims and survivors of abuse and violence. The article also explores the ways in which women have learnt to not only survive but to resist violence. Additionally women have seen the violence against their bodies in the light of the violence done to the earth. It concludes with a brief reference to postcolonial scholarship on violence against women and a challenge to all women to discover together where the word of liberation lies for all women as we struggle to find a violence free world.